Prediksi Penjualan Handphone di Toko X menggunakan Algoritma Regresi Linear - Yubi Aqsho Ramadhan; Ahmad Faqih; Gifthera Dwilestari (Jurnal Informatika Terpadu, 2023)
Mobile phones or smartphones have become a basic necessity in life. This device has transformed how we communicate and access information, and entertainment, making our lives easier and more comfortable. Store X sells mobile phones from various brands. The purpose of this research is to predict the sales of handphones in the next three months based on the sales data of brand X. Linear regression is used as the prediction method, with the number of handphones sold as the Y variable and the sales period as the X variable. RMSE (Root Mean Squared Error) and Relative Error are used to evaluate the prediction results. The predicted sales for the Entry category in the first month are 84 units, 86 units in the second month, and 88 units in the third month, while for the Mid category, 28 teams are sold in the first month, 29 teams in the second month, and 30 units in the third month. The RMSE evaluation result for the Entry category is 10.36, while the Relative Error value is 19.11%, and the RMSE value for the Mid category is 7.50, while the Relative Error value is 32.97%. The prediction of handphone sales using this linear regression method can be classified as sufficient or usable.